Pemantauan Konsentrasi Partikulate Matter (PM10) pada Udara Ambien di Pasar Andounohu Kota Kendari - Sari, Karmila; Rosdiana, Rosdiana; Sumarlin, Sumarlin (Universitas Muhammadiyah Kendari, 2021)
Particulate Matter (PM10) is a term for solid or liquid particles found in the air. The PM10 will scatter sunlight so that it interferes with the view. It is classified as particulate aerodynamics with a diameter of fewer than 10 m resulting from human activities, mostly from motor vehicles and industry. In this study aims to determine the concentration of PM10 in ambient air at Andounohu Market, Kendari. The concentration of PM10 at four points in the Andounohu market, Poasia Village, Andounohu District, Kendari City showed that the location of point 1 is 3.6573 g/Nm3, point 2 is 3.18696 g/Nm3, point 3 is 2,3581 g/Nm3, point 4 is 5.2936 g/Nm3. From the results of measurements made of PM10 concentrations at 4 points in the Andounohu market, Poasia Village, Andounohu District, Kendari City, it shows that PM10 in ambient air is still below the ambient air quality standard according to the State Government Regulation of the Environment No. 12 of 2010.